Impact of power outages: Unveiling their influence on micro, small, and medium-sized enterprises and poverty in Sub-Saharan Africa - An in-depth literature review - Timothy King Avordeh; Adam Salifu; Christopher Quaidoo; Rockson Opare-Boateng (Heliyon, 2024)
The paper explores the review on the impact of electricity outages on MSMEs in Sub-Saharan Africa, analyzing their effects on productivity and poverty levels based on a review of 102 studies spanning from 2010 to 2023. The review organizes the studies by subject, theme, and major research findings to analyze the impact of power outages in Sub-Saharan Africa on poverty reduction. Power outages in the region hinder income generation and employment, perpetuating the cycle of poverty. The key findings emphasize the importance of proactive action to minimize the negative consequences of power outages on small businesses and poverty. MSMEs face disruptions that lead to reduced productivity, operational inefficiencies, higher production costs, and supply chain disruptions. Strategies to lessen power outage effects on MSMEs, the review proposed promoting energy source diversification, such as renewables. The research review concludes that power outages are a major challenge for MSMEs and energy diversification is a key solution to reduce poverty in the region.